(untitled) (Archaeologia Adriatica, 2013)
A concise overview of the Chair in Prehistoric Archaeology of the former Faculty of Philosophy in Zadar, present-day University of Zadar, is given. Emphasis is placed on main achievements of excavations, with brief overview of each excavated site.